A Review on Building Resilient Power Networks: Emphasizing Adjacent Span Dynamics - Tawsif Ahmad; Manisha Maharjan; Fernando Bereta Dos Reis; Jennifer Appiah-Kubi; Vishvas H. Chalishazar; Sraddhanjoli Bhadra (IEEE Access)
This research article presents a comprehensive review of resilience in power transmission and distribution (T&D) systems, focusing on key studies that examine structural integrity, mechanical stress distribution, and system reliability under various conditions. The primary objective is to investigate the dynamics of adjacent spans and their role in influencing stress distribution and structural resilience of poles and towers through the cables connecting them. The article synthesizes findings across multiple studies, covering assumptions, system topologies, methodologies, and challenges that affect resilience in these networks. Particular attention is given to identifying studies that address the influence of adjacent spans and tower-line interactions, as these factors play a crucial role in the stress distribution and structural dynamics within poles, towers, and transmission lines. In addition to identifying critical factors contributing to system vulnerability, this review emphasizes the importance of continued research to better understand and mitigate risks from extreme events, such as high winds combined with ice storms, which pose significant risks to the stability and reliability of electricity supply. By consolidating knowledge on current challenges and future needs, this work outlines future directions to advance resilience studies and contributes to ongoing efforts to strengthen power T&D networks, reducing disruptions in electricity supply and improving overall system resilience in an evolving climate landscape.